Stepped light-induced transient measurements of photocurrent and voltage in dye-sensitized solar cells based on ZnO and ZnO:Ga - Goncalves, Agnaldo de Souza [UNESP]; Davolos, Marian Rosaly [UNESP]; Masaki, Naruhiko; Yanagida, Shozo; Mori, Shogo; Nogueira, Ana F. (American Institute of Physics (AIP), 2009)
In order to explain the higher short-circuit current (J(sc)) with comparable open-circuit voltage (V(oc)) from dye-sensitized solar cells (DSCs) based on gallium-modified ZnO (ZnO:Ga) porous electrodes, the diffusion coefficient (D) and electron lifetime (tau) in DSCs with and without Ga-modified ZnO were studied by stepped light-induced transient measurements of photocurrent and voltage. In comparison to DSCs based on ZnO electrodes, the ZnO:Ga-based solar cells provided lower D and higher tau values. The results were interpreted according to the transport-limited recombination model, where the Ga modification induced a higher density of intraband charge traps. At matched electron densities, a decrease in V(oc) from DSCs based on ZnO:Ga was observed, suggesting a positive shift of the ZnO:Ga conduction band edge. The higher J(sc) can be explained by the positive shift of the ZnO:Ga conduction band edge in addition to the increased roughness factor of the electrode due to the Ga modification. (C) 2009 American Institute of Physics. [doi:10.1063/1.3226073]